Wali Nikah dalam Perspektif Empat Madzhab - Hidayat, Syaiful (Ali Muchasan, 2017)
The guardian is one of the most important elements in marriage. The existence of a guardian becomes a decisive one in the case of legitimacy of his / her marriage. In the view of some people, perhaps a person's trustworthiness is considered too great, given the right of a guardian who can force his child to be married off without should seek approval from the child. With the pretext of freedom to choose their own spouse, so many people judge that the right of guardians in modern times needs to be reviewed and some even think it is unfit to apply.This short article trying to parse the view by exposing the opinions of the scholars about the right and position of the guardian in marriage.